Development Solar Cell Trainer (SCT) as Learning Media on Renewable Energy - Sukardi Sukardi; Agung Samudra; Ahmad Eko Suryanto; Syarpin Syarpin (VANOS Journal of Mechanical Engineering Education, 2023)
Starting from the limitations of learning media on renewable energy material, the idea of developing a Solar Cell Trainer (SCT) was sparked. The purpose of this research is to develop a SCT as a learning media on renewable energy material that can help the learning process become easy and fun. This research is a Research and Development (R&D) which aims to produce a SCT and test its effectiveness. The effectiveness of the SCT trainer is seen from the aspects of Content, Learning Communication Media, Implementation Power and User Response. The R&D procedure is divided into 3 stages, namely: preliminary studies, product development, and evaluation and revision. The object of research involved 1 media expert lecturer and 35 students as users. The data collection technique used a questionnaire which then the results were analyzed descriptively. The results showed that the content and media aspects of learning communication were in the good category with a score of 82.5; while the implementation power and user response to the SCT media were in the good category with a score of 80.9. The conclusion of this research shows that SCT media is suitable for use in learning.